Comparison of pneumonitis risk between immunotherapy alone and in combination with chemotherapy: an observational, retrospective pharmacovigilance study - Li, Huixia; Zheng, Yifan; Xu, Peihang; Li, Zimu; Kuang, Yukun; Feng, Xiaoqing; He, Junhao; Li, Jia; Chen, Xiao; Bai, Lihong; Tang, Ke-Jing (Frontiers in Pharmacology, 2023)
Importance Checkpoint inhibitor pneumonitis (CIP) is a rare but serious adverse event that may impact treatment decisions. However, there is limited information comparing CIP risks between immune checkpoint inhibitor (ICI) monotherapy and combination with chemotherapy due to a lack of direct cross-comparison in clinical trials. Objective To determine whether ICI combination with chemotherapy is superior to ICI in other drug regimens (including monotherapy) in terms of CIP risk. Study Design and Methods This observational, cross-sectional and worldwide pharmacovigilance cohort study included patients who developed CIP from the World Health Organization database (WHO) VigiBase and the US Food and Drug Administration Adverse Event Reporting System (FAERS) database. Individual case safety reports (ICSR) were extracted from 2015 to 2020 in FAERS and from 1967 to 2020 in Vigibase. Main outcomes and measures Timing and reporting odds ratio (ROR) of CIP in different treatment strategies were used to detect time-to-onset and the risk of pneumonitis after different immunotherapy regimens. Results A total of 93,623 and 114,704 ICI-associated ICSRs were included in this study from Vigibase and FAERS databases respectively. 3450 (3.69%) and 3278 (2.86%) CIPs occurred after therapy initiation with a median of 62 days (VigiBase) and 40 days (FAERS). Among all the CIPs, 274 (7.9%) and 537 (16.4%) CIPs were associated with combination therapies. ICIs plus chemotherapy combination was associated with pneumonitis [ROR 1.35, 95% Cl 1.18-1.52]. The combination of anti-PD-1 antibodies and anti-CTLA-4 antibodies with chemotherapy demonstrated an association with pneumonitis in both Vigibase [PD-1+chemotherapy: 1.76, 95 %CI 1.52-2.05; CTLA-4+chemotherapy: 2.36, 95%Cl 1.67-3.35] and FAERS [PD-1+chemotherapy: 1.70, 95%CI 1.52-1.91; CTLA-4+chemotherapy: 1.70, 95%Cl 1.31-2.20]. Anti-PD-L1 antibodies plus chemotherapy combinations did not show the association. Conclusion Compared to ICI in other drug regimens (including monotherapy), the combination of ICI plus chemotherapy is significantly associated with higher pneumonitis toxicity. Anti-PD-1/CTLA4 medications in combination with chemotherapy should be obviated in patients with potential risk factors for CIP. Trial Registration Combination of immune checkpoint inhibitors plus chemotherapy and risk of pneumonitis: an observational, retrospective pharmacovigilance study, ChiCTR2200059067.